THE EFFECT OF HEALTH EDUCATION USING AUDIO VISUAL METHODS ON ANEMIA PREVENTION EFFORTS IN ADOLESCENT GIRLS AGES 15-17 YEARS AT WALISONGO HIGH SCHOOL - Emi Linawati; Titik Suhartini; Iit Ermawati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Health education is an effort to influence/invite other people (individuals, groups, and communities) to behave in a healthy life, which in the process of health education is influenced by materials/materials, learning environment, educational devices both software and hardware and learning subjects ( individuals, groups, families, communities and health workers). Anemia occurs due to a micronutrient deficiency of iron (Fe). Health education is expected to increase efforts to prevent anemia so that it can reduce the prevalence of anemia. The purpose of the study was to analyze the effect of health education with audio-visual methods on efforts to prevent anemia in adolescent girls aged 15-17 years at Walisongo High School, Laweyan Village, Sumberasih District, Probolinggo Regency.The design of this research is pre-experimental research with One-Group Pretest-Posttest Design approach. The population in this study were students of class X, XI, XII at SMA Walisongo with as many as 30 teenage girls and the number of samples as many as 30 teenage girls. Sampling technique using Total Sampling. Collecting data using a questionnaire then the data is processed using SPSS using the Spearman rank test.The results of the analysis of anemia prevention efforts in the poor category before being given health education were 26 respondents (86.67%), while after being given health education, anemia prevention efforts in the good category were 22 respondents (73.33%). The results of the analysis of the value of health education with the audio-visual method on efforts to prevent anemia are 0.000 (less than 0.05), so there is an effect of health education with the audio-visual method on efforts to prevent anemia in adolescents aged 15-17 years in SMA Walisongo.It is hoped that Walisongo High School can conduct health education on efforts to prevent anemia on an ongoing basis with related parties in order to reduce the risk of anemia in adolescent girls aged 15-17 years.